Proceedings of the 2021 International Conference on Management of Data 2021
DOI: 10.1145/3448016.3457296
|View full text |Cite
|
Sign up to set email alerts
|

Fast Parallel Algorithms for Euclidean Minimum Spanning Tree and Hierarchical Spatial Clustering

Abstract: This paper presents new parallel algorithms for generating Euclidean minimum spanning trees and spatial clustering hierarchies (known as HDBSCAN * ). Our approach is based on generating a wellseparated pair decomposition followed by using Kruskal's minimum spanning tree algorithm and bichromatic closest pair computations. We introduce a new notion of well-separation to reduce the work and space of our algorithm for HDBSCAN * . We also present a parallel approximate algorithm for OPTICS based on a recent sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Other practical cases based on MST include COVID-19 pandemic transmission forecasting [141], clustering [142], constructing trees for broadcasting [143], image registration and segmentation [144], circuit design [145] and emotion recognition [146]. There do exist several primary algorithms, namely, classic algorithm and faster algorithm; however, in consideration that such MST-like models will facilitate the development of multifarious industrial areas, more and more individuals have turned to design a variety of intuitive algorithms to figure out such issues, such as reinforcement learning [147], genetic algorithm [148] and fast parallel algorithm [149].…”
Section: Minimum Spanning Treementioning
confidence: 99%
“…Other practical cases based on MST include COVID-19 pandemic transmission forecasting [141], clustering [142], constructing trees for broadcasting [143], image registration and segmentation [144], circuit design [145] and emotion recognition [146]. There do exist several primary algorithms, namely, classic algorithm and faster algorithm; however, in consideration that such MST-like models will facilitate the development of multifarious industrial areas, more and more individuals have turned to design a variety of intuitive algorithms to figure out such issues, such as reinforcement learning [147], genetic algorithm [148] and fast parallel algorithm [149].…”
Section: Minimum Spanning Treementioning
confidence: 99%
“…, where > 0 is fixed and MST(R) is the exact minimum spanning tree [3], [87]. The most recent approaches [88] focus on developing parallel algorithms for the construction of MST(R).…”
Section: Minimum Spanning Tree For Any Finite Metric Spacementioning
confidence: 99%
“…Besides the linkage criteria considered in this paper, other popular criteria for HAC include single, centroid, and median linkage. Single linkage with the Eulidean metric is closely related to the Euclidean minimum spanning tree problem, and can be solved efficiently using variants of Boruvka's algorithm for minimum spanning tree [49,67]. Centroid and median linkage do not satisfy the reducibility property and cannot take advantage of the NNC algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…Unfortunately, exact HAC algorithms usually require Ω(𝑛 2 ) work, since the distances between all pairs of points have to be computed. To accelerate exact HAC algorithms due to their significant computational cost, there have been several parallel exact HAC algorithms proposed in the literature [25,33,35,43,44,59,67,70], but most of them maintain a distance matrix, which requires quadratic memory, making them unscalable to large data sets. The only parallel exact algorithm that works for the metrics that we consider and uses subquadratic space is by Zhang et al [70], but it has not been shown to scale to large data sets.…”
Section: Introductionmentioning
confidence: 99%